Bisphenol A exposure triggers endoplasmic reticulum stress pathway leading to ocular axial elongation in mice - Chen, Junhan; Ikeda, Shin-ichi; Kang, Longdan; Negishi, Kazuno; Tsubota, Kazuo; Kurihara, Toshihide (Frontiers in Medicine, 2023)
Background Ocular axial elongation is one of the features of myopia progression. Endoplasmic reticulum (ER) stress-associated scleral remodeling plays an important role in ocular axial elongation. Bisphenol A (BPA) is one of the most common environmental pollutants and is known to affect various human organs through ER stress. However, whether BPA exerts an effect on scleral remodeling remains unknown. The purpose of this study was to determine the effect of BPA on the development of myopia and scleral ER stress. Methods BPA was administered by intraperitoneal injection. 4-PBA was administered as an endoplasmic reticulum stress inhibitor by eye drops. Refraction and axial length were measured by refractometer and SD-OCT system. Western blot was performed to detect the expression level of ER stress-related proteins. Results BPA-administered mice exhibit axial elongation and myopic refractive shift with endoplasmic reticulum stress in the sclera. BPA administration activated scleral PERK and ATF6 pathways, and 4-PBA eye drops attenuated ER stress response and suppressed myopia progression. Conclusion BPA controlled axial elongation during myopia development in a mouse model by inducing scleral ER stress and activation of the PERK/ATF6 pathway. 4-PBA eye drops as ER stress inhibitor suppressed BPA-induced myopia development.